2023
DOI: 10.1039/d3va00057e
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plastic economy: a perspective and a call for international action

Abstract: The current plastic circular economy lacks a uniform framework. It overfocuses on recycling, reuse and energy recovery. An enhanced plastic economy drives innovation and concerted effort in reducing plastic pollution and waste management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The guide may capture the elements of circular economy by incorporating aspects related to more efficient use of resources from the design to the end-of-life management of a product or from the inception to the delivery/ commissioning/ decommissioning of a service or project. This could contribute to waste minimization and reduction of greenhouse gas emissions [39,40]. The guide may also promote human rights reporting through explicitly including the relevant indicators.…”
Section: Aspects Of Disclosurementioning
confidence: 99%
“…The guide may capture the elements of circular economy by incorporating aspects related to more efficient use of resources from the design to the end-of-life management of a product or from the inception to the delivery/ commissioning/ decommissioning of a service or project. This could contribute to waste minimization and reduction of greenhouse gas emissions [39,40]. The guide may also promote human rights reporting through explicitly including the relevant indicators.…”
Section: Aspects Of Disclosurementioning
confidence: 99%
“…Plastics are widely used in many sectors and everyday life because they are durable, lightweight, and affordable. This widespread use results in a significant release of plastic waste into the environment [1,2]. Currently, the majority of the world's plastic materials derive from eight primary polymers, with polyethylene (PE) and polypropylene (PP) making up 45% of these polymer outputs [3].…”
Section: Introductionmentioning
confidence: 99%
“…While it is uncertain how MPs could affect human health, a study using a human adenocarcinoma cell line found polystyrene (PS) MPs to be weakly embryotoxic [17]. Therefore, in addition to MPs removal, it is equally important to ensure plastic waste is properly reduced and managed and environmentally friendly plastic substitutes are developed to minimize the consumption of conventional plastics, hence the volume of waste generated [18,19].…”
Section: Introductionmentioning
confidence: 99%